1987
DOI: 10.1159/000234188
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Murine IgE Responses with Amino Acid Polymer/Allergen Conjugates

Abstract: Serum IgE antibody responses were generated in mice by intranasal exposure to grass pollen extract. Primary IgE responses were suppressed by the concomitant intranasal administration of a conjugate of polysarcosine and pollen extract which has been shown to be a potent tolerogen when given parenterally. Partial suppression of boosted IgE responses was observed when the conjugate was applied intranasally with a secondary challenge of unmodified extract. The data suggest that clinical schedules of intranasal app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Administration of antigen by the i.n. route has been shown to induce IgE responses in a variety of systems (Holt et al, 1981a;McCaskill et al, 1982McCaskill et al, , 1984Enander et al, 1985;Henderson et al, 1985Henderson et al, , 1987Takafuji et al, 1987Takafuji et al, , 1989Tamura et al, 1994a). The magnitude of the IgE response varies from system to system and is sometimes dependent on adjuvant administration.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of antigen by the i.n. route has been shown to induce IgE responses in a variety of systems (Holt et al, 1981a;McCaskill et al, 1982McCaskill et al, , 1984Enander et al, 1985;Henderson et al, 1985Henderson et al, , 1987Takafuji et al, 1987Takafuji et al, , 1989Tamura et al, 1994a). The magnitude of the IgE response varies from system to system and is sometimes dependent on adjuvant administration.…”
Section: Discussionmentioning
confidence: 99%
“…[92] The reduced IgE response was transient [93] and was attributed partly to a short-lived antigen-specific T cell suppression. [94] It was further demonstrated that intranasal application of the conjugate can reduce the serum IgE antibody response that was brought about through exposure to the grass pollen extract, [95] providing a method to treat allergy. Kimura et al…”
Section: Immunogenicitymentioning
confidence: 99%
“…First, hints toward the nonimmunogenicity of poly­(sarcosine) (PSR) were given by Blout et al as early as 1959 . Later, in a series of papers which appear to have been largely forgotten, Moran and co-workers investigated PSR conjugates to allergens such as grass pollen extract. It was found that PSR-conjugation was suitable to suppress an immune response to an antigen after antigen conjugation.…”
Section: Applications Of (Poly)peptoidsmentioning
confidence: 99%
“…In the last communication of this series, the level of serum IgE was also followed in mice intranasally exposed to grass pollen . The mice were also treated with a conjugate of PSR to grass pollen.…”
Section: Applications Of (Poly)peptoidsmentioning
confidence: 99%